Analisis Kerusakan Jalan C. Bangas Kota Palangka Raya: Damage Analysis of C. Bangas Road Palangka Raya City - Febryanto, Listyo Endar; Puspasari, Nirwana; Permana, Ari Widya (Media Ilmiah Teknik Sipil, 2024)
Roads are land transportation which is the main supporting factor for the entire community, especially in the economic sector and other social activities. The damage to the C. Bangas road is like road damage in general, namely that there are many holes in the road caused by rainwater which .will flood the road. This research was carried out using 2 (two) methods, namely the Pavemanet Condition Index (PCI) and the Surface Distress Index (SDI) Method. The research was carried out along Jalan C. Bangas, Palangka Raya City, with a road length of 875 meters and divided into 18 segments with 50 meter intervals. The results of the research will be compared between the 2 (two) methods used. From the results of the research conducted, there are differences in the level of road damage in the PCI and SDI methods. The average PCI value for all roads is 17,278. The PCI value indicates that the condition of the road surface is serious, so it is necessary to upgrade/reconstruct the road. The average SDI value for all roads is 51,389. The SDI value indicates the road surface condition is Medium. So it is necessary to carry out routine maintenance. With this it can be concluded that the 2 (two) methods used got different results, namely the PCI method got serious results (severe damage) and the SDI method got moderate results (moderate damage)..